2015
DOI: 10.1093/bja/aeu373
|View full text |Cite
|
Sign up to set email alerts
|

Difficult intubation in obese patients: incidence, risk factors, and complications in the operating theatre and in intensive care units

Abstract: Current controlled trials. Identifier: NCT01532063.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(142 citation statements)
references
References 42 publications
2
126
0
14
Order By: Relevance
“…The risk of intubation difficulty is two-fold higher in the obese patients [4]. Fat deposition around the neck and large tongue in obese patients complicate laryngoscopic view and intubation [5].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of intubation difficulty is two-fold higher in the obese patients [4]. Fat deposition around the neck and large tongue in obese patients complicate laryngoscopic view and intubation [5].…”
Section: Discussionmentioning
confidence: 99%
“…Patient files and electronic hospital database were evaluated to identify patient demographic aspects and comorbid conditions ( , absence of teeth, limited mouth opening (<3 cm), limited neck movement and short neck, presence of dentures, and presence of obstructive sleep apnea (OSA) 3,7 was collected from the routine standard form filled in by the anesthesiologists during preoperative visit and during induction of anesthesia. As our standard records also include reliable information concerning induction of anesthesia and mask ventilation difficulty rated by staff anesthesiologist in a standardized manner, we were able to classify patients into three separate groups with respect to difficulty in airway management as follows: DMV (Han's mask ventilation classification grade 3 or 4 mask ventilation) 10 ; DL (grade 3 or 4 laryngoscopic view or ≥4 intubation attempts) 11 ; and DMV combined with DL.…”
Section: Methodsmentioning
confidence: 99%
“…So, the anesthetic management of those patients may remain challenging. While there are many reports comparing the anesthetic complications between obese and lean patients [3][4][5][6][7][8] , there is no report whether further increase in BMI has additional implication, and which bedside screening test is more meaningful for predicting DMV and DL when only obese group is considered. The aim of this study was to evaluate DMV and DL in this unique group of adult obese patients with endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, tracheal intubation is more difficult in obese patients with obstructive apnea syndrome, with an incidence close to 15 to 20% (versus 2 to 5% in the general population), and associated with the severity of the obstructive apnea syndrome [26]. A recent study reported an increase in the incidence of difficult intubation in obese patients [3]. Moreover, in this study, elevated Mallampati score, limited mouth opening, reduced cervical mobility, presence of an obstructive apnea syndrome, coma and severe hypoxemia (risk factors included in the MACOCHA score [27]) were associated with difficult intubation in obese patients.…”
Section: Intubationmentioning
confidence: 98%